2016
DOI: 10.1177/1558944715626930
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wrist Function After Simulated Total Wrist Arthrodesis

Abstract: There is poor consensus in the literature regarding associated functional limitation and the preferred wrist position for total wrist arthrodesis. The purpose of the current investigation was twofold: (1) to assess the functional limitations of wrist arthrodesis and (2) to determine the optimal position for wrist arthrodesis using a simulated wrist fusion model. Twenty healthy volunteers underwent simulated wrist arthrodesis in 6 different positions using custom-molded wrist splints: 15° extension with 0° radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…3A-B). Yuvaraj et al [33] showed improved grip strength with ulnar deviation, but other studies on grip strength after wrist fusion have suggested that positioning the wrist in extension offers better strength; however, these studies did not demonstrate any benefit of ulnar deviation [6,8]. Therefore, in our study, we maintained wrist dorsiflexion at 10°to 15°as before, which was consistent with the most functional position after fusion in previous reports [10,18] (Fig.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…3A-B). Yuvaraj et al [33] showed improved grip strength with ulnar deviation, but other studies on grip strength after wrist fusion have suggested that positioning the wrist in extension offers better strength; however, these studies did not demonstrate any benefit of ulnar deviation [6,8]. Therefore, in our study, we maintained wrist dorsiflexion at 10°to 15°as before, which was consistent with the most functional position after fusion in previous reports [10,18] (Fig.…”
Section: Introductionsupporting
confidence: 89%
“…Some loss of grip strength is expected with a wrist fusion when compared with the normal side. In addition to reports supporting wrist dorsiflexion [3, 6, 8, 11-13], we reasoned that grip strength could be slightly improved by further radializing the translocated ulna and aligning it with the second metacarpal joint to achieve ulnar deviation, as demonstrated by Yuvaraj et al [33]. The loss of grip strength from using the second metacarpal was less than the outcomes reported by Vyas et al [29] and Qu et al [21] (loss of 29% grip strength in operated limb).…”
Section: Discussionmentioning
confidence: 84%
“…15 On the contrary, Hinds et al said that the position of fusion did not affect the grip strength or satisfaction. 11 In our case, the position of the wrist could be changed by different degrees by bending the K wires after they had been introduced into the bone (Fig. 3).…”
Section: Discussionmentioning
confidence: 88%
“…Some authors have advocated arthrodesis without a bone graft, [1][2][3] whereas others recommended the bone graft. [4][5][6][7] Various fixation devices have also been reported, including K wires or Steinmann pins, 4,7-10 staples, 1 screws, 11 and compression plates. 7,12 However, the rate of successful fusion and the incidence of complications have varied greatly.…”
Section: Introductionmentioning
confidence: 99%
“…However, Larsson noted that a little extension and ulnar deviation boosted grip power [ 29 ]. On the other hand, the fusion posture did not influence grip strength or contentment, according to Hinds et al [ 30 ]. Our study’s average postoperative hand position of patients following wrist arthrodesis was 17.5 degrees of extension and 6 degrees of ulnar deviation.…”
Section: Discussionmentioning
confidence: 90%